Performansi Motor Bakar Berbahan Bakar Limbah B3 (Oli Bekas) Sepeda Motor Jenis Sae 10w-40 Sebagai Bahan Bakar Alternatif - Irvan Gunawan; Iwan Kurniawan; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Waste (B3) used oil is a residue of pure oil that comes from many kind of industrial activities and engine means. After waste oil is converted to fuel without special treatment. waste oil can be used as fuel for the internal combustion engine. The engine diesel is modified in the fuel filter system and the addition of the fuel pump. Filter system use fuel filter which is positioned parallel with two filtering stages. In the first stage the filter is given a magnet to pull the iron powder that is contained on the oil and the second filter has the function to filter out of the whole of the dirt that causes the nozzle to clog. This Fuel Pump serves to supply waste lubricant oil into the fuel injection system. Performance characteristics performed by testing a diesel engine at a constant speed of 2100 rpm. The harvesting start from 350 W. 700 W. 1000 W. 1350 W. 1700 W. 2000 W . 2350 W. 2700 W. and 3000 W with a variation of time of 3.5 minutes per loading on fuel consumpion. From the experimental results show the performance of diesel engine with used fuel oil waste does not change in power. Torque. and BMEP. Thermal efficiency of the bioslar obtained 18.54% and thermal efficiency in used oil 17.72%. Keywords : Waste Engine Oil. Diesel Engine. Filter. Pump